Effects of different algal feed concentration on the growth and survival rates of hatchery-produced juvenile ball sea cucumber, Phyllophorus proteus (Bell 1884) (Echinodermata: Holothuroidae Dendrochirotida) - Lescano, Marien Mapa (2016.)
The study compared growth and survival rates of juvenile Ball Sea Cucumbers (Phyllophorus proteus) fed with three different concentrations of the microalgae Chaetoceros calcitrans (T1: 1x105 cells/mL, T2: 2 x 105 cells/mL and T3: 4 x 105 cells/mL). Survival Rate (SR, %) was recorded daily while Specific Growth Rate (SGR, % day-1) and Growth rate (GR, mm day-1) were calculated based on change in length, width, and volume in 19 days. Positive growth in length, width, and volume was observed in all treatments. However, only SGR in volume showed significant difference among treatments (p<0.05). The lowest SGR, SR, and GR were observed in juveniles fed with the highest concentration. Thus, the feeding concentrations 1-2x105cells/mL may be the optimal feeding concentration for Phyllophorus proteus juveniles.
Special Problem -- Bachelor of Science in Biology. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Phyllophorus proteus; Chaetoceros calcitrans; Dendrochirotid; Sea cucumber